School-recorded special educational needs provision in children with major congenital anomalies: a linked administrative records study of births in England, 2003-2013 - Peppa, Maria; Lewis, Kate Marie; De Stavola, Bianca; Hardelid, Pia; Gilbert, Ruth; on behalf of the HOPE study (International Journal of Population Data Science, 2025)
Background Children with major congenital anomalies (MCAs) disproportionately experience complex health problems requiring additional health and educational support. Objectives To describe survival to the start of school and recorded special educational needs (SEN) provision among children with and without administrative record-identified MCAs in England. We present results for 12 system-specific MCA subgroups and 25 conditions. We also describe the change of prevalence in recorded SEN provision before and after SEN reforms in 2014, which were implemented to improve and streamline SEN provision. Methods We created a birth cohort of 6,180,400 singleton children born in England between 1 September 2003 and 31 August 2013 using linked administrative records from the ECHILD database. MCAs were identified using hospital admission and mortality records during infancy. SEN provision in primary school was defined by one or more recording of SEN provision in state-school records during years 1 to 6 (ages 5/6 years to 10/11 years). Results Children with any MCA had a 5-year survival rate of 95.1% (95% confidence interval (CI) 95.0, 95.2) compared with 99.7% (95% CI 99.7, 99.7) among children without an MCA. 41.6% (75,381/181,324) of children with an MCA had any recorded SEN provision in primary school compared with 25.7% (1,285,572/5,008,598) of unaffected children. Of the 12 system-specific MCA subgroups, children with chromosomal, nervous system and eye anomalies had the highest prevalence of recorded SEN provision. The prevalence of recorded SEN provision decreased by 4.8% (99% CI -5.4, -4.3) for children with any MCA compared with a reduction of 4.2% (99% CI -4.3, -4.2) for unaffected children, when comparing pupils in year 1 before and after 2014. Conclusion We observed that approximately two fifths of children with MCAs have some type of SEN provision recorded during primary school, but this proportion varied according to condition and declined following the 2014 SEN reforms, similar to children unaffected by MCAs.